Rancang Bangun Sistem Pengukur Jarak Pada Mesin Produksi Berpenggerak Leadscrew T8 Menggunakan Rotary Encoder KY-040 - NAAFIAN, MUFID; SYAFITRI, NIKEN (e-Proceeding FTI, 2024)
Measurement is an important aspect in production process, development of digital measuring tools is really useful for supporting the effectiveness of the production process in industry sector. In this research, distance measuring tools is designed and attached to production machines such as lathe, milling, and drill to read the distance displacement from chisel blades to each of these machines. Rotary Encoder KY-040 will be used and installed with countershaft and level by using coupling on production machines so it can rotate according to the direction of coupling rotation. The measurement on three different references produce different accuracy level and precision. The smallest average precision is 0.02 (interval 1 mm), the biggest average precision is 4.46 (interval 10 mm) while the smallest average accuracy is 0.03 (interval 1 mm) and the biggest accuracy is 6.43 (interval 10 mm). The result of the measured distance will be displayed on LCD screen so production machine operator can read measured distance directly and easily. Keywords: Arduino UNO, LCD, Measurement, production machine, Rotary Encoder KY-040 ABSTRAK Pengukuran merupakan aspek penting dalam proses produksi, pengembangan alat ukur berupa alat ukur digital sangat dibutuhkan guna menyokong efektifitas proses produksi pada sektor industri. Dalam penelitian ini dirancang sebuat sistem alat ukur jarak yang dipasang pada mesin produksi seperti bubut, frais, dan bor untuk membaca perpindahan jarak dari pisau pahat dari masing-masing mesin tersebut. Rotary Encoder KY-040 akan digunakan dan terpasang dengan as penggerak dan engkol menggunakan kopel pada mesin produksi, sehingga dapat berputar sesuai dengan gerak arah putaran engkol. Pengukuran pada tiga jarak referensi berbeda menghasilkan tingkat akurasi dan presisi sistem yang bervariatif, dengan rataan presisi terkecil 0,02 (interval 1 mm) dan terbesar 4,46 (interval 10 mm) sedangkan rataan akurasi terkecil 0,03 (interval 1 mm) dan terbesar 6,43 (interval 10 mm). Hasil jarak terukur akan ditampilkan pada layar LCD sehingga operator mesin produksi dapat membaca jarak terukur secara langsung. Kata kunci: Arduino UNO, LCD, mesin produksi, Pengukuran, Rotary Encoder KY-040.